Human Ascaris infection is associated with higher frequencies of IL-10 producing B cells. - Josefina Zakzuk; Juan F Lopez; Cezmi Akdis; Luis Caraballo; Mübeccel Akdis; Willem van de Veen (Public Library of Science (PLoS), 2024)
Introduction Ascaris lumbricoides has dual effects on the immune system of infected hosts. The IgE response to this parasite has been thoroughly studied, but little is known about cellular responses induced by infection. This study aims to explore the interplay between A. lumbricoides infection and B cell responses, especially B regulatory cells. Methods Participants from Santa Catalina, Bolívar, Colombia, a helminth-endemic town, were screened for soil-transmitted helminthiasis (STH) using stool examinations. Eighteen A. lumbricoides-infected and 11 non-infected subjects were selected. Blood samples were analyzed for Breg cells and related cytokines, and immunoglobulins specific to the A. lumbricoides excretory/secretory product, ABA-1. Results Infected subjects exhibited higher frequencies of Breg cells, especially those with a higher A. lumbricoides egg burden. Higher frequencies of different Breg subsets were observed in infected individuals, with CD25+CD71+CD73- B cells being notably increased in strongly infected individuals. Additionally, A. lumbricoides infection was associated with reduced levels of circulating ABA-1-specific IgG1 and IgE. IL-10+ B cell frequencies correlated inversely with ABA-1-specific IgE. Conclusions A. lumbricoides infection has a significant impact on the immune response, particularly on Breg cell populations and antibody responses. Our findings suggest that A. lumbricoides infection mediates a dose-dependent immunosuppressive response characterized by an increase in Breg cells and concomitant suppression of ABA-1-specific humoral responses.